ANALISIS PERAN TRADISI NYAER TERHADAP DINAMIKA PERILAKU SOSIAL DI LOMBOK - ANDRI KURNIAWAN (Universitas Islam Negeri (UIN) Mataram, 2019)
Abstract The mission of the spread of Islam in Lombok was previously carried out with da'wah including an approach that was given a touch of cultural aesthetics, such as the Nyaer oral tradition that still survives today. The formulation of this research problem is how the dynamics of social behavior as a reaction to the Nyaer tradition? and what is the role of the Nyaer tradition in community life? This study identified the role of Nyaer as a media for cultural propaganda in Lombok. The existence of this tradition is then analyzed in the role angle in social life. Interesting in this article when analyzing the role and moral messages contained in the tradition of the real life is the potential to be preserved. The role is not only as a medium of cultural preaching, but also as an educational medium and contains entertainment value in the vision of virtue. Keywords: Role, The Nyaer Tradition, Preaching Media, Social Behavior